Xenotransplantasi Unsur Khinzir sebagai Medium Terapeutik Menurut Perspektif Islam dan Saintifik - Abdul Rahman, Noor Naemah; Mohamad, Mohd Afifuddin (IKIM Press, Institute Of Islamic Understanding Malaysia, 2016)
Man and pig have an almost similar physiology. This similarity is found in the physiological systems that provides certain health benefits in particular as a therapeutic medium. The suitability of porcine-based tissues and cells for xenotransplantation at that point in time only involve heart valves, β cells, renal cells, hepatic cells and porcine insulin. Other parts are deemed unsuitable due to rejection by the human body and the inability to function normally. This article used the method of content analysis to look at the suitability of using porcine-based elements in certain situations as outlined in Islam. From this analysis, it is found that, while both man and pig have similar physiological systems, this does not mean that porcinebased elements are allowed to be used in normal circumstances in Islam unless its usage is governed by the principle of darurah. The use of porcine-based elements is only allowed in high risk situations which endanger the life of man if porcine-based elements are not used.